Promoting Vocational Education. A Guide for Vocational Educators - West Virginia State Dept. of Education, Charleston. Bureau of Vocational, Technical, and Adult Education; West Virginia State Dept. of Education, Charleston. Bureau of Vocational, Technical, and Adult Education ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This guide for vocational educators suggests some effective approaches to public relations. First, it briefly discusses effective public relations, human interest, a public relations sense, and contacts. The guide then covers the news media, focusing on the preparation of news articles and on radio and television announcements (relative to types of programs), making a television appearance, and who to contact (includes sample news releases and spot announcements). Discussed next is taking photographs and preparing a slide show, including writing the script, making the slides, and presenting the show. Finally, brochures, newsletters (includes suggested basic layouts), exhibits or displays, open houses, and speeches are covered. (EM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Aids; Guides; Mass Media; News Media; Public Relations; Publicize; Radio; School Community Relationship; Slides; Television; Vocational Education; Guides, General